Direito indígena à terra: uma análise da legislação e da jurisprudência à luz da cosmovisão indígena - Exner, Camila Katurchi (2024)
Human rights enshrine the values that are important for every human being to have a dignified life. Nowadays, the aim is to give specific protection to marginalized and vulnerable people, in order to best safeguard the rights of these minorities, among which are indigenous peoples. For some years now, national laws and international declarations and conventions have been created to protect indigenous peoples, providing them with a legal framework that recognizes their self-determination and their own way of life. These regulations, accompanied by national case law (especially from the Federal Regional Court of the 1st Region and the Federal Supreme Court) and international case law (considering the Inter-American Court of Human Rights), understand that indigenous people have a worldview that is distinct from modernity, which is extremely important for interpreting human rights from an indigenous perspective. That said, in the midst of land conflicts in Brazil, questions began to be asked about what the criteria should be for defining whether or not land should be demarcated in favor of indigenous peoples: the indigenato theory or the theory of indigenous fact (the temporal milestone thesis). Based on legislation and jurisprudence, both national and international, it will be seen, from a decolonial perspective, that the temporal milestone thesis cannot subsist, under penalty of affronting the human dignity of indigenous people